Efficacy and safety of reduced-port laparoscopic surgery versus conventional laparoscopic surgery for colorectal cancer - Zhi-min Liu; Qi-jun Yao; Fengyun Pei; Fang He; Yandong Zhao; Jun Huang (BMC Cancer)
Abstract Background Laparoscopic radical resection has become the most important treatment for resectable colorectal cancer (CRC). However, there is still a lack of researches on the efficacy and safety of reduced-port laparoscopic surgery (RPLS) versus conventional laparoscopic surgery (CLS) in the treatment of CRC. Patients and methods From January 2019 to July 2022, 698 patients with CRC received surgical treatment in the Sixth Affiliated Hospital of Sun Yat-sen University were enrolled in this retrospective cohort study. Patients were divided into RPLS group (n = 220) and CLS group (n = 478) according to their surgical procedures. Propensity score matching (PSM) was used to adjust the differences in baseline characteristics. The incidence of perioperative outcomes and survival rates related results were analyzed after PSM. Results Four hundred twenty-two patients were equally divided into RPLS group (n = 211) and CLS group (n = 211) after PSM. There were no statistically significant differences in overall survival (OS) and progression-free survival (PFS) between the two groups (P value was 0.773 and 0.579 respectively). The perioperative outcomes of patients between the two groups were comparable, except that patients in the RPLS group had a shorter postoperative hospital stay (P value < 0.001). Conclusion For patients with CRC, both RPLS and CLS might be acceptable surgical options. No significant differences in perioperative outcomes, PFS rates and OS rates were observed between the two groups. For certain cases, RPLS was superior to CLS in terms of postoperative recovery.